2013
DOI: 10.1111/hae.12209
|View full text |Cite
|
Sign up to set email alerts
|

The risk of elective orthopaedic surgery for haemophilia patients: Japanese single-centre experience

Abstract: Haemophilic arthropathy causes pain and a severely restricted range of motion, and results in a significant reduction in quality of life. When conservative treatments have failed, orthopaedic surgery is recommended for these patients with severe haemophilic arthropathy. However, surgery for haemophilia patients is challenging due to high complication rate such as infection, delayed wound healing and mortality. The aim of this study was to evaluate the incidence of early complications and identify preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…However, in our experience, the quality of life can be improved via diminished pain, even under situations of stationary contractures. Also, the risk for deep infection seemed smaller than reported previously 2,3 .…”
contrasting
confidence: 57%
“…However, in our experience, the quality of life can be improved via diminished pain, even under situations of stationary contractures. Also, the risk for deep infection seemed smaller than reported previously 2,3 .…”
contrasting
confidence: 57%
“…There are varying outcome measures that have been used to assess the success of perioperative management in haemophilia patients: haemostatic outcome, rate of treatment complications (eg postoperative bleeding, wound infections) and treatment mortality …”
Section: Resultsmentioning
confidence: 99%
“…Of note, the assessment of perioperative mortality is complicated even as a short‐term outcome measure in surgery in patients with haemophilia, particularly due to underlying comorbidities related to viral disorders (HIV, HCV) in older patients with haemophilia likely to undergo major orthopaedic procedures. The study by Hirose of 118 procedures in 80 patients reported an overall mortality within 6 months of 6.2% (five patients) . However, this included one patient who died preoperatively, and the principal drivers of mortality were associated with severe liver disorders due to HCV hepatitis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, though symptomatic improvement may be achieved with the latest antiviral drugs in HIV-infected patients, a cure is not possible. Particularly with respect to hepatitis C, postoperative death cases are significantly higher among cases characterized as Child classification B, those with low ascites and albumin, and those with thrombocytopenia [9]. Confirmation of these conditions is important for surgical decisions.…”
Section: Surgery In Hcv-and Hiv-infected Patientsmentioning
confidence: 99%